Convergent and Distinct Effects of Multisensory Combination on Statistical Learning Using a Computer Glove - Madan, Christopher R.; Singhal, Anthony (Frontiers in Psychology, 2021)
Learning to play a musical instrument involves mapping visual+auditory cues to motor movements and anticipating transitions. Inspired by the serial reaction time task and artificial grammar learning, we investigated explicit and implicit knowledge of statistical learning in a sensorimotor task. Using a between-subjects design with four groups, one group of participants were provided with visual cues and followed along by tapping the corresponding fingertip to their thumb, while using a computer glove. Another group additionally received accompanying auditory tones; the final two groups received sensory (visual or visual+auditory) cues but did not provide a motor response—all together following a 2×2 design. Implicit knowledge was measured by response time, whereas explicit knowledge was assessed using probe tests. Findings indicate that explicit knowledge was best with only the single modality, but implicit knowledge was best when all three modalities were involved.